Effects of Different Physiotherapy Programs on the Respiratory Function of Individuals with Chronic Obstructive Pulmonary Disease - Skirmantaitė, Indre; Kupčiūnaitė, Laura (Slauga. Mokslas ir praktika, 2025)
The article analyzes the effects of virtual reality sessions and breathing exercises performed in a physical therapy room on the respiratory function of individuals with chronic obstructive pulmonary disease. The disease is often defined as progressive and causing structural and functional changes in the respiratory system, which causes shortness of breath, cough, chest pain, drowsiness, and fatigue, which negatively affects the quality of life. Physiotherapy has been found to be an effective treatment method which improves the lung function, increases the functional capacity, as well as the respiratory muscle strength, and reduces the shortness of breath. In the scientific literature, the application of virtual reality is mainly discussed in cases of neurological diseases, but there are few studies that analyze the application of this method in cases of respiratory system diseases. The study sample: purposive sampling: 10 study participants with mild to moderate disease. The following methods were used in the research: analysis of scientific information sources, testing, descriptive and comparative data analysis. After summarizing the results of the study, it was found that both applied physiotherapy programs are more effective, but greater changes in the respiratory system were recorded in the group of study participants who completed virtual reality classes.